To determine the level of satisfaction on current readership towards KOSMO! / Siti Aishah Abdulah Safer - Abdulah Safer, Siti Aishah (Faculty of Business and Management, 2007)
This research has been conducted for the purpose of 'To Determine the level of satisfaction on current readership towards KOSMO!'. KOSMO! The first ever compactsize daily in MaIaysia which presents a new concept that combines a daily and a magazine into one was launched on 30 August 2004 by the Prime Minister, YAB Dato' Seri Abdullah Haji Ahmad Badawi. The main objective this research was to identify the factors that influence KOSMO! customers or readership to become loyal. Furthermore, to determine whether KOSMO! fulfiII the customer's expectctions and to determine whether KOSMO! Fulfill the customer's satisfaction. For the purpose of the study, an exploratory research design has been adopted. The 50 respondents of the study were in the Klang Valley. The researcher has used non-probability sampling as the sampling technique. In this study, descriptive statistics had been used to interpret the data such as reliability test, frequency analysis and crosstabulation analysis. From the findings, the respondents are agreeing with the factors that can influence the customers or readers to become loyal. Beside, KOSMO! fulfill customer expectations and customers satisfaction because of the attractiveness and ability to attract customers. In order to make KOSMO! to be successful that can attract a lot of readers, all the comments and suggestions indicate in the open ended questions should be count up.